Design and implementation of two surveys targeted at describing fouling communities and identifying non-native species within active ports. (15th December 2020) - Holmes, Samuel; Callaway, Ruth
Abstract: Ports have long been considered 'high-risk' areas for the introduction of non-native species (NNS) and should therefore be a focus of NNS monitoring. The industrial nature of active ports can, however, provide various problems when attempting to carry out monitoring programmes. Current methodologies designed to identify NNS and to describe fouling communities have not been developed specifically for use in active ports and can encounter a number of issues when used in these environments. Here, two surveys were developed and trialled within an active port in South Wales, UK, designed to describe fouling communities, identify NNS and overcome some of the major limitations to conducting surveys within ports. Over a 6-month period, fouling communities dominated by solitary ascidians developed in each survey. Seven NNS were identified, mostly species already recorded in the 1950s, including the Mediterranean crab Brachynotus sexdentatus, and the more recently introduced Japanese skeleton shrimp Caprella mutica . Each survey was evaluated independently with respect to key factors, including the ability to detect NNS and practical aspects of using these survey methods in an applied context. We conclude that whilst each survey can function independently, the use of both survey types in conjunction offers the most robust solution to identifying NNS and describing wider fouling communities within active ports. This research has implications for the future monitoring and management of NNS within UK ports.